PERSEPSI GURU PAI TERHADAP KOMPETENSI 6C ERA SOCIETY 5.0 - Syifanaya Firdausi, Kharisma; Hanif Indra Maulana; Laila Badriyah (Pendidikan Agama Islam, 2024)
Era of society 5.0, 6 basic literacy skills are needed, such as data literacy, namely the ability to read, analyze and use information (big data) in the digital world. Then technological literacy, understanding how machines work, technological applications (coding, artificial intelligence, machine learning, engineering principles, biotech), finally human literacy, namely humanities, communication and design, where technology is developing rapidly causing changes in the way of looking at concepts. education. The competencies required in the world of education are also changing. This affects the competencies possessed by prospective teachers. They must prepare, improve and continue to hone their competencies in order to be able to produce a quality generation that is able to answer the challenges of the increasingly sophisticated 5.0 era. This research aims to explain the role of prospective PAI teachers, explaining the 6C competencies which are a renewal in the 5.0 era curriculum where previously they were known as 4C competencies but now the Minister of Education and Culture has added two new competencies to become 6C competencies, as well as the challenges faced by prospective PAI teachers in the 5.0 era. The methods used in this research are qualitative descriptive methods and literature studies. The results and discussion of this research found that: 1. From the role of prospective PAI teachers, many do not yet know about the 6C competencies that are being promoted by the Minister of Education and Culture because they have not yet become a focus among educators. 2. Prospective educators try to hone their competencies to face the 5.0 era.